2011
DOI: 10.1242/dev.056002
|View full text |Cite
|
Sign up to set email alerts
|

Ral GTPase promotes asymmetric Notch activation in the Drosophila eye in response to Frizzled/PCP signaling by repressing ligand-independent receptor activation

Abstract: Ral is a small Ras-like GTPase that regulates membrane trafficking and signaling. Here, we show that in response to planar cell polarity (PCP) signals, Ral modulates asymmetric Notch signaling in the Drosophila eye. Specification of the initially equivalent R3/R4 photoreceptor precursor cells in each developing ommatidium occurs in response to a gradient of Frizzled (Fz) signaling. The cell with the most Fz signal (R3) activates the Notch receptor in the adjacent cell (R4) via the ligand Delta, resulting in R3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 46 publications
(44 reference statements)
0
25
0
Order By: Relevance
“…This form of ligand-independent Notch cleavage has been observed in fly eye disks where in developing ommatidia, R3 precursor cells express the Notch ligand Delta and signal to the adjacent R4 precursors to become R4 cells. 2 Cho and Fischer recently determined that Ral GTPase prevents ligand-independent activation of Notch in pre-R3 cells, 18 demonstrating the importance of regulating the different types of Notch cleavage. The first ADAM 10 homolog to be characterized in the context of Notch cleavage was the product of the Drosophila gene kuzbanian (kuz).…”
mentioning
confidence: 99%
“…This form of ligand-independent Notch cleavage has been observed in fly eye disks where in developing ommatidia, R3 precursor cells express the Notch ligand Delta and signal to the adjacent R4 precursors to become R4 cells. 2 Cho and Fischer recently determined that Ral GTPase prevents ligand-independent activation of Notch in pre-R3 cells, 18 demonstrating the importance of regulating the different types of Notch cleavage. The first ADAM 10 homolog to be characterized in the context of Notch cleavage was the product of the Drosophila gene kuzbanian (kuz).…”
mentioning
confidence: 99%
“…Nevertheless, we determined that loss of Ral activity results in Notch receptor activation independent of ligand binding. 19 The main evidence for this lies in four observations. First, the specific defects in Ral mutant eyes were typical …”
Section: Ral Inhibits Ligand-independent Notch Signaling In Drosophilamentioning
confidence: 96%
“…30,32 We found that Ral defines a distinct pathway by which R3 is biased to become the Delta signaling cell. 19 In response to Frizzled activation, elevated Ral activity in R3 prevents ligand-independent Notch activation in pre-R3, thereby helping to tip the scales in favor of pre-R3 becoming the signaling cell. The main evidence for this idea is 2-fold.…”
Section: Ral Inhibits Ligand-independent Notch Signaling In Drosophilamentioning
confidence: 99%
See 2 more Smart Citations